Óxido de Fe e Al no deslocamento vertical de P em neossolos regolíticos - Carneiro, Kalline de Almeida Alves (2019)
The family farming areas of the municipalities of Esperança and Remigio, located in the Paraiba State Agreste, present as predominant soil the Regosol, with low availability of P and N, limiting crop productivity. To alleviate these nutrient deficiencies, organic fertilizers, especially cattle manure, are widely used by farmers. However, manure rates are applied empirically, often beyond necessary. Due to the excessive application of manure P is accumulated in the surface layer and released by vertical transport, causing eutrophication that generates economic and environmental damage. Given the above, it is necessary to study the vertical transport of P in the Regosols. Due to the levels of iron (Fe) and aluminum (Al) oxides that can adsorb P, even in small amounts, directly influence the availability of this nutrient in the soil. The objective of this work was to evaluate the influence of Fe and Al oxides on sorption and miscible phosphorus displacement in areas fertilized and not fertilized with bovine manure and to relate them to the mineralogy and physicochemical factors of a eutrophic Regosol of Paraíba State Agreste region. Nine properties of family farmers were selected. Then a simple systematic random sampling was performed with the fixation of ten sampling points for each area, taking deformed soil samples at a depth of 0 - 10 cm, totaling 90 samples. After collection, the soil samples were physicochemical and mineralogical characterization (XRD and FRX). In all soil samples, were determined the sorption parameters of P. To achieve the proposed objectives two experiments were installed: In experiment I - P soil miscible displacement - The potential for P losses in columns of P was evaluated in fertilized and non-fertilized areas with bovine manure, and the influence of the amorphous and crystalline Fe and Al oxides contents on P. In experiment II - Soil samples from the nine selected areas were packed in columns and hydrodispersive soil characterization was performed using KBr. The miscible P displacement, native plus the inorganic P (P pulse), was evaluated in the vertical transport of P in the soil samples of the nine selected areas, whose numerical adjustment was performed using the Stanmod software. After the miscible displacement of P the column soils were used to determine P desorption by successive extraction of P adsorbed with the use of iron strips. The data from experiment II were submitted to first order pseudo-equation k-adsorption and desorption kinetic models. With the results of soil physical, chemical and mineralogical analyzes, and of experiments I and II, it was possible to organize three chapters: Chapter I - “Leaching of xviii P in Regosols in Family Farming Areas of the Semiarid Region”: In all areas it was observed that most of the P was removed up to 20 pore volume, which is equivalent to 40 mm of water monthly precipitation. High rates of manure for consecutive years resulted in a high loss of soil phosphorus (> 6.0 mg L-1). Chapter II - “P transport dynamics in Eutrophic Regosol”. The hydrodispersive characterization data with potassium bromide (KBr) confirmed its chemical non-equilibrium with the soil, representing a good tracer. There was a lower P leaching in columns with similar Fe and Al contents, being related to the increase of P adsorption capacity unlike the soil samples with varied Fe and Al contents, which presented a higher P displacement. Chapter III - "P sorption kinetics in Eutrophic Regosol in family farming areas". The highest P adsorption rate occurred in soil samples with varying Fe and Al contents, referring to the municipality of Esperança. While the behavior of phosphate desorption curves were identical for all areas, regardless of manure fertilization, desorbed phosphate decreased exponentially. The areas of Esperança, regardless of whether they were fertilized or not, showed a higher rate of phosphorus adsorption by Fe and Al oxides and a decrease in P. leaching. In the fertilized and non-fertilized areas in Remigio with similar Fe and Al contents, the kinetics of phosphate adsorption and desorption were similar to those of Esperança. Remigio areas showed higher desorption rate than adsorption rate and an increase in P leaching, indicating that this adsorption was influenced by the presence of goethite (Gt) in the clay fraction, by the low rates of P via organic fertilization and also because the soil itself has very low initial P levels when compared to the areas of Esperança. In this study, it is evident that the P leaching in a sandy soil is an environmental risk, because the soil mineralogy presents predominantly negative charges.